Low- Income housing : a critique of Federal aid - Taggart, Robert III (Batimore ; London : JohnHopkins Press, 1970)
This study analyzes the existing federal subsidy programs. It reviews their intended purposes and accomplishments to date, and it suggests ways they should be used and improved in the future
sju 22/01/2019
Loans
Keywords: Housing